Progressive Reduction of Iconic Gestures Contributes to School-Aged Children’s Increased Word Production - Mertens, Ulrich J.; Rohlfing, Katharina J. (Frontiers in Psychology, 2021)
The economic principle of communication, according to which successful communication can be reached by least effort, has been studied for verbal communication. With respect to nonverbal behavior, it implies that forms of iconic gestures change over the course of communication and become reduced in the sense of less pronounced. These changes and their effects on learning are currently unexplored in relevant literature. Addressing this research gap, we conducted a word learning study to test the effects of changing gestures on children’s slow mapping. We applied a within-subject design and tested 51 children, aged 6.7 years (SD = .4), who learned unknown words from a story. The storyteller acted on the basis of two conditions: In one condition, in which half of the target words were presented, the story presentation was enhanced with progressively reduced iconic gestures (PRG); in the other condition, half of the target words were accompanied by fully executed iconic gestures (FEG). To ensure a reliable gesture presentation, children were exposed to a recorded person telling a story in both conditions. We tested the slow mapping effects on children’s productive and receptive word knowledge three minutes as well as two to three days after being presented the story. The results suggest that children’s production of the target words, but not their understanding thereof, was enhanced by PRG.